Poly(vinylidene Fluoride-Hexafluoropropylene) Porous Membrane with Controllable Structure and Applications in Efficient Oil/Water Separation - Wang, Xinya (Materials (Basel), 2018)
Poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) porous membranes are fabricated via thermally induced phase separation (TIPS) with mixed diluent (dibutyl phthalate (DBP)/dioctyl phthalate (DOP)). The effects of mixed diluent are discussed in detail in term of morphology, mean pore size, selective wettability, etc. The results show that the membrane structure changes from spherulitic to bicontinuous with the change of DBP/DOP ratio. It is also found that the degree of crystallization decreases with the decrease of DBP/DOP ratio in mixed diluent. When liquid–liquid (L-L) phase separation precedes solid–liquid (S-L) phase separation, the obtained membranes have outstanding hydrophobicity and lipophilicity, excellent mechanical property. Additionally, the PVDF-HFP hybrid membranes are prepared with silica (SiO(2)) particles and the effect of SiO(2) content on structure and properties is discussed. It is found that the PVDF-HFP hybrid membrane with 2 wt % SiO(2) (M3-S2) has better properties and higher filtration rate and separation efficiency for surfactant-stabilized water-in-oil emulsion separation. Moreover, the membrane M3-S2 also exhibits excellent antifouling performance for long-running.